Evidence for Adaptive Introgression of Disease Resistance Genes Among Closely Related Arabidopsis Species. Issue 8 (1st August 2017) - Bechsgaard, Jesper; Jorgensen, Tove Hedegaard; Schierup, Mikkel Heide
Abstract: The generation and maintenance of functional variation in the pathogen defense system of plants is central to the constant evolutionary battle between hosts and parasites. If a species is susceptible to a given pathogen, hybridization and subsequent introgression of a resistance allele from a related species can potentially be an important source of new immunity and is therefore expected to be selected for in a process referred to as adaptive introgression. Here, we survey sequence variation in 10 resistance ( R -) genes and compare them with 37 reference genes in natural populations of the two closely related and interfertile species: Arabidopsis lyrata and A. halleri . The R -genes are highly polymorphic in both species and show clear signs of trans -species polymorphisms. We show that A. lyrata and A. halleri have had a history of limited introgression for the reference genes. For the R -genes, the introgression rate has been significantly higher than for the reference genes, resulting in fewer fixed differences between species and a higher sharing of identical haplotypes. We conclude that R -genes likely cross the species boundaries at a higher rate than reference genes and therefore also that some of the increased diversity and trans -specific polymorphisms in R -genes is due to adaptive introgression.